Formation of volatile sulfur compounds and S-methyl-l-cysteine sulfoxide in Brassica oleracea vegetables. (30th July 2022) - Friedrich, Katharina; Wermter, Nicole S.; Andernach, Lars; Witzel, Katja; Hanschen, Franziska S.
Highlights: S-methyl-l -cysteine sulfoxide (SMCSO) was quantified in white and red cabbages. Volatile organic sulfide formation from SMCSO was followed. S-Methyl-methanethiosulfinate is the main sulfide found in Brassica homogenates. Volatile organic sulfides formation correlates with cystine lyase abundance. Abstract: Besides glucosinolates, Brassica vegetables accumulate sulfur-containing (+)- S -methyl-l -cysteine sulfoxide (SMCSO, methiin), mainly known from Allium vegetables. Such (+)- S -alk(en)yl-l -cysteine sulfoxides can degrade to volatile organosulfur compounds (VOSCs), which have been linked to health beneficial effects. In the present study, the accumulation of SMCSO and the formation of VOSCs was investigated in Brassica oleracea vegetables. SMCSO content of commercially available white and red cabbages was monitored over a three-month period and linked with the formation of VOSCs. S -Methyl methanethiosulfinate was the main VOSC released from SMCSO. Upon heating, it degraded to dimethyltrisulfide and dimethyldisulfide, which were less abundant in fresh homogenates. SMCSO made up approximately 1% of the dry matter of cabbages and the overall contents were similar in white and red cabbages (3.2–10.2 and 3.9–10.3 µmol/g fresh weight, respectively). Using proteome profiling it was shown that recovery of VOSCs correlated with abundance of two isoforms of cystine lyase.